2021
DOI: 10.1128/jvi.01666-21
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies Virus Infection Triggers NF-κB Activation via the DNA Damage Response but Actively Inhibits NF-κB-Dependent Gene Expression

Abstract: The nuclear factor kappa B (NF-κB) pathway is known to integrate signaling associated with very diverse intra- and extracellular stressors including virus infections, and triggers a powerful (pro-inflammatory) response through the expression of NF-κB-regulated genes. Typically, the NF-κB pathway collects and transduces threatening signals at the cell surface or in the cytoplasm leading to nuclear import of activated NF-κB transcription factors. In the current work, we demonstrate that the swine alphaherpesviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 76 publications
7
21
0
Order By: Relevance
“…Hypomethylated genes were also enriched in NF-κB signaling pathway. PRV triggered the activation of NF-κB signaling pathway through DNA damage response, and viral late factors could effectively inhibit NF-κB-dependent genes expression (Romero and Favoreel, 2021), which might also be regulated by m 6 A modification. PRV infection might regulate the expression of these cytokines by changing m 6 A modification, and the specific mechanism needed further study.…”
Section: Discussionmentioning
confidence: 99%
“…Hypomethylated genes were also enriched in NF-κB signaling pathway. PRV triggered the activation of NF-κB signaling pathway through DNA damage response, and viral late factors could effectively inhibit NF-κB-dependent genes expression (Romero and Favoreel, 2021), which might also be regulated by m 6 A modification. PRV infection might regulate the expression of these cytokines by changing m 6 A modification, and the specific mechanism needed further study.…”
Section: Discussionmentioning
confidence: 99%
“…PRV infection [ 18 ] and the RAGE-HMGB1 axis [ 33 ] could all induce the inflammatory response by activating the signaling pathway of NF-κB. To further investigate the anti-inflammatory function of AGDP during PRV infection, the effects of AGDP on the activities of IκBα and P65 proteins were further explored, which are thought of as the important checkpoints in the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB signaling can be activated by various stimulus factors and has thus typically resulted in a robust surge of several proinflammatory factors, along with negative feedback factors to inhibit excessive inflammation [ 15 , 16 ]. Additionally, two recent studies have addressed the fact that PRV infection could trigger a non-canonical NF-κB pathway independent of IKKβ kinase activity, which would not result in the expression of tumor necrosis factor alpha (TNF-α) or interleukin-6 (IL-6), and not induce the negative-feedback-loop genes, such as IκBα [ 17 , 18 ]. These studies indicated that PRV could efficiently inhibit the potentially antiviral response of hosts by triggering the activation of a non-canonical DDR-NF-κB signaling axis, but these results could not exclude the other potential signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The DDR-NF-κB signaling axis requires the expression of viral proteins but is initiated before active PRV replication. However, late PRV proteins inhibit NF-κB-dependent gene expression [ 85 ].…”
Section: Prv Infection Inhibits Ifn-i Productionmentioning
confidence: 99%